Being a male caregiver for a wife with a colorectal cancer ostomy: Challenges and possibilities - Neto, Pablo José Idelbrando de Oliveira; Fava, Silvana Maria Coelho Leite; Filipini, Cibelle Barcelos; Andrade, Maria Betânia Tinti de; Dázio, Eliza Maria Rezende; Chini, Lucélia Terra (Seven Editora, 2023)
Objective: Recognize the men's care livings of the wife with an ostoma by colorectal cancer (CCR). Method: This is an exploratory study, descriptive, qualitative, in which the wholeness care consisted of the theoretical axis, with the interview conducted by the question: "Say how is it for you to care for your wife/partner with an intestinal stoma." The database was analyzed under the theoretical reference proposed through the analysis of content inductive. Results: Four men participated in this study. From the testimonies, were created two categories: "The approach of the man to care" and "Living on how we can". In the first, on the illness of the woman, the spouse takes many functions, from the finances to the hedge of familiar attention, between the children, to fit on woman's needs. On the second, we learned how hard is for men to accept the role of the spouse with an ostomy from a cancer caregiver. Conclusion: We learned that are a lot of challenges founds by the men caregivers of a spouse with an intestinal stoma by the CCR. The support provided by the men is very important and opens a window of possibilities to the coping and treatments of a woman with CCR. DOI:https://doi.org/10.56238/devopinterscie-202